Financial Performance Analysis of PT Waskita Karya Related to Its Initial Public Offerings Stock Price and Future Prospect - Lukmana, Marlisa; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2013)
This final project attempted to analyze Waskita Karya decision to get the fund from initial public offerings, analyzes the factors that caused Waskita Karyaâ€™s IPO share oversubscribed until 800%, analyze the prospect of Waskita Karya by forecasting its stock price at the end 2013 with using Discounted Cash Flow (DCF) and Relative Valuation method. Moreover, author also give recommendation for investor and management of Waskita Karya related to its capital structure in order to maximize its firm value.Â Keywords: Initial Public Offerings (IPO), Discounted Cash Flow method, Relative Valuation, Capital Structure, Construction Industry, State-Owned Company